Garden State gangland: the rise of the mob in New Jersey - Deitche, Scott M. (Rowman & Littlefield, 2018)
Introduction -- The Newark Family -- Dry years in Jersey -- Zwillman -- Dutch, Longy, Jerry, and the Boot -- The Moretti hit -- The Decavalcantes -- On the wire -- Bayonne Joe -- Bruno and the Down Neck mob -- The Genovese family -- The SCI -- The big bet -- South Jersey war -- The Eagle and video gambling -- On the docks -- The receding tide